Pelatihan Pembuatan dan Pengelolaan Website Program Studi Matematika - Amalina Amalina; Darvi Mailisa Putri; Syarto Musthofa; La Ode Sabran; Reihani Jemila Nurbai (IKIP PGRI Bojonegoro, 2023)
ABSTRACTOptimalization of public information and web-based academic services is a service activity carried out by the Service Team of the Mathematics Study Program of UIN Imam Bonjol Padang. The purpose of this service is as an effort to open public information to the wider community, especially study program partners and to students as users. The general public can access information about the study program through the website generated from this activity. In addition, students can use the website as a means to access academic services. Applications for thesis supervisors, proposal seminar submissions, and thesis hearings can be made through the website. The target of the activity is students and the wider community who need information related to the study program. The activity stages include identifying the research question, gathering the information to answer the question, analyzing and interpreting the information and sharing the results with the participants. This community service resulted in a mathematics study program website that provides information to the public regarding mathematics study programs and provides academic services to students of mathematics study programs Keywords: Public Information, Academic Services, Website ABSTRAKOptımalısası ınforması publık dan layanan akademık berbasıs websıte merupakan kegiatan pengabdian yang dilaksanakan oleh Tim Pengabdian dari Program Studi Matematika UIN Imam Bonjol Padang. Tujuan pengabdian ini adalah sebagai upaya keterbukaan informasi publik kepada masyarakat luas khusunya mitra program studi dan kepada mahasiswa sebagai pengguna. Masyarakat luas dapat mengakses informasi mengenai program studi melalui website yang dihasilkan dari kegiatan ini. Selain itu, mahasiswa dapat menggunakan website sebagai sarana untuk mengakses layanan akademik. Permohonan pembimbing skripsi, pengajuan seminar proposal, dan sidang skripsi dapat dilakukan melalui website. Sasaran kegiatan adalah mahasiswa dan masyarakat luas yang membutuhkan informasi terkait program studi. Tahapan kegiatan meliputi mengidentifikasi pertanyaan penelitian, mengumpulkan informasi untuk menjawab pertanyaan, menganalisis dan menafsirkan informasi dan membagikan hasilnya kepada partisipan. Pengabdian kepada masyarakat ini menghasilkan website program studi matematika yang memberikan informasi kepada masyarakat terkait prodi matematika dan memberikan layanan akademik kepada mahasiswa prodi matematika. Kata Kunci: Informasi Publik, Layanan Akademik, Website